The causal role of breakfast in energy balance and health: a randomized controlled trial in obese adults - Chowdhury, Enhad A.; Richardson, Judith D.; Holman, Geoffrey D.; Tsintzas, Kostas; Thompson, Dylan; Betts, James A. (American Society for Nutrition, 2016)
Background: The causal nature of associations between breakfast and health remain unclear in obese individuals. Objective: We sought to conduct a randomized controlled trial to examine causal links between breakfast habits and components of energy balance in free-living obese humans. Design: The Bath Breakfast Project is a randomized controlled trial with repeated measures at baseline and follow-up among a cohort in South West England aged 21–60 y with dual-energy X-ray absorptiometry–derived fat mass indexes of $13 kg/m2 for women (n = 15) and $9 kg/m2 for men (n = 8). Components of energy balance (resting metabolic rate, physical activity thermogenesis, diet-induced thermogenesis, and energy intake) were measured under free-living conditions with random allocation to daily breakfast ($700 kcal before 1100) or extended fasting (0 kcal until 1200) for 6 wk, with baseline and follow up measures of health markers (e.g., hematology/adipose biopsies). Results: Breakfast resulted in greater physical activity thermogenesis during the morning than when fasting during that period (difference: 188 kcal/d; 95% CI: 40, 335) but without any consistent effect on 24-h physical activity thermogenesis (difference: 272 kcal/d; 95% CI: 2254, 798). Energy intake was not significantly greater with breakfast than fasting (difference: 338 kcal/d; 95% CI: 2313, 988). Body mass increased across both groups over time but with no treatment effects on body composition or any change in resting metabolic rate (stable within 8 kcal/d). Metabolic/cardiovascular health also did not respond to treatments, except for a reduced insulinemic response to an oral-glucose-tolerance test over time with daily breakfast relative to an increase with daily fasting (P = 0.05). Conclusions: In obese adults, daily breakfast leads to greater physical activity during the morning, whereas morning fasting results in partial dietary compensation (i.e., greater energy intake) later in the day. There were no differences between groups in weight change and most health outcomes, but insulin sensitivity increased with breakfast relative to fasting.